In utero exposure to persistent and nonpersistent endocrine-disrupting chemicals and anogenital distance. A systematic review of epidemiological studies. Issue 2 (17th October 2019) - Nelson, William; Liu, Ding-Yuan; Yang, Yin; Zhong, Zhao-Hui; Wang, Ying-Xiong; Ding, Yu-bin
Abstract: Anti-androgenic endocrine-disrupting chemicals (EDCs) can cross the placenta to modify early offspring sexual dimorphic markers. These changes are linked to anogenital distance (AGD), which is an androgen-sensitive anthropometric parameter used as a biomarker of perineal growth and caudal migration of the genital tubercle. This review aimed to summarize strength of evidence for associations of in utero exposure to EDCs with AGD and to identify gaps and limitations in the literature so as to inform future research. We performed an electronic search of English literature in September 2019 in medical literature analysis and retrieval system online (MEDLINE), Web of Science and Toxline. We included epidemiological studies that examined in utero exposure to persistent and nonpersistent EDCs and considered AGD in offspring as an outcome. Our review contained 16 investigations examining exposure to persistent EDCs (nine studies) and nonpersistent EDCs (seven studies). Some individual studies reported an inverse association between exposure to bisphenol A (BPA), dioxins, perfluoroalkyl substances, and organochlorides and AGD in both male and female offspring. Meta-analysis of three studies found a small reduction of AGD in female offspring exposed to BPA. The number of studies per chemical is small, and number of subjects examined is limited; so, replication of these results is needed. To achieve more specificity and better replication of results, future studies should establish the association of nonpersistent EDCs using multiple urine samples, evaluate the cumulative impact of exposure to a mixture of anti-androgenic chemicals, and offer adequate consideration of more maternal- and children-related confounding factors. Abstract : Early-life exposure to anti-androgenic endocrine disrupting chemicals provide inconsistent findings demonstrating an inverse association between higher maternal levels of some chemicals and anogenital distance, the effect being more common in male offspring.